Erysipelothrix rhusiopathiae infection in pigs, pork and raw pork handlers in Kamuli District, Eastern Uganda - Musewa, A.; Roesel, Kristina; Nakanjako, D.; Grace, Delia; Ssenyonga, R.; Nangendo, J.; Kawooya, I.; Erume, J. (International Livestock Research Institute, 2016)
Erysipelothrix rhusiopathiae is a zoonotic ubiquitous gram-positive bacterium, which causes erysipelas in swine, mammals, birds and erysipeloid in humans. People in contact with animals, animal products or animal wastes are at greatest risk. From June 2013 to December 2015, a multidisciplinary risk assessment was conducted to identify the risks associated with E. rhusiopathiae along the pig value chain in Kamuli District, Eastern Uganda. Quantitative and qualitative methods of data collection were employed. Serum from 460 pigs and 100 fresh pork samples and human EDTA blood was gathered from 302 raw pork handlers (butchers, abattoir workers and housewives), for microbiology cultures and serology. Six focus group discussions were conducted with 26 butchers/abattoir workers and with 26 housewives. Three key informant interviews were conducted with a health assistant, veterinary officer and a nursing officer. Overall, 308/460 (67%) of the pig sera carried antibodies against E. rhusiopathiae. Forty-five percent (45/100, 45%) of the fresh pork samples were contaminated with E. rhusiopathiae and 30/302 (9.9%) of the raw pork handlers were positive for infection with E. rhusiopathiae. The mean age of the raw pork handlers was 38 years, 21/30 (70%) of men were infected compared to 9/30(30%) of the women. The main risk factor for the infection was the type of raw pork handler. Of the abattoir workers 14/38 (47%) were positive, 9/59 (30%) of the butchers and 7/205 (23.3%) of the housewives were infected with E.rhusiopathiae. This is the first ever report of E. rhusiopathiae in pigs and humans in Uganda and East Africa. Previously, the acute form of swine erysipelas may have been confused for other diseases in pigs reported in Uganda which are characterized acute symptoms such as sudden death (for example, African swine fever). We recommend increasing awareness of the disease among animal and human practitioners as treatment is easy and available and vaccination is possible. However, the disease is still unknown to local veterinarians, clinical doctors, meat inspectors, butchers and laboratory personnel. Proper hygiene, regular pork inspection, use of protective wear among people working/ in contact with animals should be promoted. The study was conducted under the Safe Food, Fair Food project led by the International Livestock Research Institute and carried out with the financial support of the Federal Ministry for Economic Cooperation and Development, Germany, and the CGIAR Research Program on Agriculture for Nutrition and Health, led by the International Food Policy Research Institute.